2014
DOI: 10.1007/s11605-014-2456-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Grade and Tumor Size are Associated with Recurrence-Free Survival in Patients with Duodenal Neuroendocrine Tumors

Abstract: Tumor grade and size are associated with recurrence-free survival in duodenal neuroendocrine tumors. When feasible, a less aggressive surgical approach to treat low-grade and low-stage duodenal NETs should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
54
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 13 publications
10
54
2
3
Order By: Relevance
“…Corresponding results were also reported in the previous studies of D-NET [5,19,22]. In addition, only 4 cases had functional or hormonal syndrome (ZES with gastrin excessive), which is also similar to previous reports; 50-98% of D-NETs present no functional syndrome despite the positive immunoreactivity for gastrin, somatostatin, and/or serotonin in majority of D-NETs [5].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Corresponding results were also reported in the previous studies of D-NET [5,19,22]. In addition, only 4 cases had functional or hormonal syndrome (ZES with gastrin excessive), which is also similar to previous reports; 50-98% of D-NETs present no functional syndrome despite the positive immunoreactivity for gastrin, somatostatin, and/or serotonin in majority of D-NETs [5].…”
Section: Discussionsupporting
confidence: 89%
“…Kim et al [22 ]also reported that 33 patients with D-NETs measuring ≤10 mm in diameter and confined to the submucosa demonstrated no recurrence following ER providing the absence of metastasis revealed by CT at the time of procedure. However, other studies did report metastasis in such tumors [11,19]. In our present study, a tumor size of 11-20 mm turned out to be a significant risk factor for metastasis compared to that of ≤10 mm; 3 patients with tumors of ≤10 mm in diameter including a case harboring only a 2-mm tumor did develop metastasis.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The manifold population of neuroendocrine neoplasms (NENs) arising in the duodenal mucosa and ampullary region has been investigated in several papers, leading to the characterization of various tumor entities according to histological structure, hormonal expression, clinical profile, genetic background and/or patient outcome [1,2,3,4,5,6,7]. Most were low-grade tumors, ranging from reportedly self-limiting gangliocytic paragangliomas (GPs) to a variety of well-differentiated epithelial neuroendocrine tumors (NETs).…”
Section: Introductionmentioning
confidence: 99%